Gagasan Al-Muallim Ar-Rabbani menurut Syeikh Ismail Lutfi Al-Fatoni - Chapakiya, Suraiya (Tanjong Malim, 2024)
Gagasan Al-Muallim Ar-Rabbani menurut Syeikh Ismail Lutfi Al-Fatoni by Chapakiya, Suraiya